Swa-Periksa Pengelolaan Budaya Perusahaan Menggunakan Sistem Audit Manajemen Sumber Daya Manusia Model General System Audit - Willy Susilo; - Eriyatno; Joko Affandi; D Agoes Goenawan (Institut Pertanian Bogor, 2012)
This article is about self assessment of corporate culture management, using system of audit for Human Resource Management (HRM) GSA model. The assessment process was done in two stages. The first stage was developing a customized assessment questionaire (tool), using semantic differential scale, involving some senior staff through Focus Group Discussion (FGD). The second stage was application of the developed devices (questionaire) to assess corporate culture management, involving a group of 30 respondents. Data obtained from the questionaire was analysed using the Importance Performance Analysis (IPA), and the result was plotted into the Cartesius diagram for interpretation. The output of the assessment was an audit report, which was prepared using the formula: True, Valua, Attractive, Policy, Location, Activity, Clauses, Evidences, Scale of Criticality, Recommendation and Time schedule (TVA PLACES ART) as a guide in the report writing. The audit report was the output of the self assessment and to be used as reference in improving HRM policy and its implementation in general and corporate culture in particular. Finally, an opinion survey was conducted to verify if the audit model was perceived to be important, beneficial, practical, feasible, and recommendable for application in the company. The result of the survey indicated that 14,2% of respondents disagree, 25,5 neutral, and 59,3 agree. These statistic figures indicate that the audit model was agreed to be important, useful, practical, feasible and recommendable for application in companies. Key words: audit report/model,corporate culture, self assessment